2019
DOI: 10.1002/app.48557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of strain and fermentation time on the production, composition, and properties of xanthan gum

Abstract: The objective of this study was to monitor the influence of Xanthomonas spp. and fermentation time on the production, properties, and composition of xanthan gum, verifying how these variables affect the biopolymer synthesis and properties. Three strains were monitored for 168 h of fermentation. Every 24 h, a sample was collected to determine cell growth, gum production, and substrate consumption. Fourier transform infrared, X‐ray diffraction, rheology, molecular characterization, thermogravimetric analysis, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…According to the data presented in Table 1, cultivation time and combination of producing strain and cultivation time have a statistically significant effect on xanthan concentration in cultivation media when biosynthesis is performed by X. campestris strains isolated from crucifers (p < 0.05). This result is in agreement with the results obtained in the research, performed in Brazil where it is confirmed that cultivation time of X. campestris strains has significant effect on xanthan productivity [17]. The mean 1, also show that effect of producing strain on xanthan concentration in cultivation media is insignificant when using strains isolated from crucifers (p > 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the data presented in Table 1, cultivation time and combination of producing strain and cultivation time have a statistically significant effect on xanthan concentration in cultivation media when biosynthesis is performed by X. campestris strains isolated from crucifers (p < 0.05). This result is in agreement with the results obtained in the research, performed in Brazil where it is confirmed that cultivation time of X. campestris strains has significant effect on xanthan productivity [17]. The mean 1, also show that effect of producing strain on xanthan concentration in cultivation media is insignificant when using strains isolated from crucifers (p > 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Besides the producing strain, cultivation time also has significant effect on xanthan quantity and quality [17]. Generally, fermentation time for xanthan production on glycerol containing media ranges from 48 h to 168 h [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, xanthan gum has a similar capacity to polymers of mineral and synthetic origin in forming pseudoplastic films, however, it has the advantage of its biological origin, in addition to the fact that it does not cause any harm to the user's health. the pseudo-plasticity effect is very important in cosmetics and was verified by (Miranda et al, 2020) during the development of the study on the characterization of different oils of natural origin, where the authors used xanthan gum as a stabilizing agent. this characteristic was also described by Abu et al (2021) during research on the properties of xanthan gum.…”
Section: Advantages and Challenges Of Xanthan Gum Over Other Materialsmentioning
confidence: 90%
“…Xanthan gum is produced by gram-negative bacteria of the genus Xanthomonas sp. of which many species have production capacity, including X. arboricola, X. axonopodis, X. campestris, X. citri, X. Fragaria, X. gummisudans, X. juglandis, X. phaseoli, and X. vasculorium (Miranda et al, 2020). However, among those mentioned, the bacterium with the highest industrial efficiency, with about 80% conversion, is X. campestris, and therefore it is generally preferred (Lei et al, 2017).…”
Section: Features Properties and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation